SUPRAVENTRICULAR RHYTHM DISTURBANCES TREATMENT WITH ANTIARHYTHMIC DRUG III CLASS NIBENTAN IN PATIENTS WITH ISCHEMIC HEART DISEASE (EXPERIMENTAL, CLINICAL AND MORPHOLOGICAL EVIDENCES) - I. A. Latfullin; R. F. Gaifullina (Столичная издательская компания, 2016)
Aim. To evaluate antiarhythmic efficiency of Nibentan (Verofarm, Russia), antiarrythmic drug III class, in supraventricular rhythm disturbances (SRD) relief in patients with ischemic heart disease (IHD). To assess morphological changes of myocardium in IHD with SRD. To specify inotropic characteristics of nibentan in experiment. Material and methods. 55 patients with IHD with different SRD were studied. 41 patients had heart failure (HF) of III functional class.14 other patients suffered acute myocardial infarction (AMI). SRD relief was achieved with 1% solution of nibentan in dose of 0.125 mg/kg patient's weight. After sinus rhythm recovery all patients received sotalol 80 mg twice a day to prevent SRD relapses. In vitro on myocardium of 10 healthy rats and 10 sliced myocardium strips of IHD patients (obtained during surgical intervention) changes in myocardium contraction intensity were assessed with PowerLab plant (ADInstruments, Australia) as a reaction on nibentan in doses of 4, 6 and 8 mkM. These doses correspond to doses of 0.125, 0.2 and 0.250 mg/kg, which are recommended for clinical practice. Histological study of autopsy materials of atrium myocardium of IHD patients with and without SRD was carried out. Phase-contrast and luminescent microscopy was also used. Results. Nibentan treatment lead to sinus rhythm recovery in 92.67% of HF patients. In 3 patients with persistent auricular fibrillation the drug was inefficient. Nibentan therapy did not result in blood pressure reduction. Heart rate decreased in 26.5%. Nibentan recovered sinus rhythm in 85.7% of AMI patients. Sinus rhythm didn't recover in 2 patients with persistent auricular fibrillation. Experimental studies revealed that myocardium contraction intensity in healthy rats increased at nibentan 4 and 6 mkM, and decreased at nibentan 8 mkM. Myocardium contraction intensity in IHD patients was decreasing while nibentan dose was growing. Histological study of auricular myocardium in IHD patients with SRD compared to myocardium in IHD patients without SRD, showed predominance of the following characteristics: fibrolipomatosis, focal and diffusive fibrosis and sclerosis, chaotic allocation of cardiac cells, muscular-elastic hyperplasia of vascular intima, contractile degeneration (at phase-contrast microscopy). Conclusion. Nibentan in bolus i.v. administration in dose of 0.125 mg/kg is effective drug for SRD relief in patients with IHD with HF and in patients with AMI. It doesn't affect BP significantly. According to data of experiments dose of nibentan 0.125mg/kg is optimal for inotropic function of myocardium. More significant histological changes in auricular myocardium can be the reason of SRD.